A Victorian architectural controversy : who was the real architect of the Houses of Parliament? - Kondō, Ariyuki (Canbridge Scholars Publishing, 2019)
Who was the bona fide architect of the New Houses of Parliament? Charles Barry (1795-1860), the winner of the Parliamentary competition, or Augustus Welby Northmore Pugin (1812-52), the 'ghost' designer, a young Catholic architect and Gothic specialist?After both men died, the controversy over the actual architect of the Houses of Parliament was to become a matter of public dispute, largely stimulated by the directly-opposed claims published by the two men's sons--the architect Edward Welby Pugin (1834-75) and Rev. Alfred Barry (1826-1910), an Anglican clergyman who later became the Bishop of.